2015
DOI: 10.1155/2015/456027
|View full text |Cite
|
Sign up to set email alerts
|

The Warthin-Like Variant of Papillary Thyroid Carcinoma: A Comparison with Classic Type in the Patients with Coexisting Hashimoto’s Thyroiditis

Abstract: Background. The Warthin-like variant of papillary thyroid (WLPTC) is a rare subtype of papillary thyroid carcinoma (PTC) resembling Warthin tumors of the salivary glands. Due to its rarity, the clinicopathologic and molecular features of WLPTC remain unclear. Methods. Of the 2,139 patients who underwent surgical treatment for PTC from 2012 to 2013, 40 patients with WLPTC were identified and compared to 200 consecutive patients with classic PTC. BRAF mutation was tested with pyrosequencing. Results. There were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
31
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 27 publications
5
31
0
1
Order By: Relevance
“…The mean nodule size was smaller than previous studies [5,6], but similar to the recent studies [8,11]. No BRAF V600E mutation was detected in patients with WVPTCs although three of nine had undergone BRAF V600E mutation analysis in this study: this trend is comparable to the findings of a previous study in which WVPTCs showed fewer mutations than conventional PTCs [11].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The mean nodule size was smaller than previous studies [5,6], but similar to the recent studies [8,11]. No BRAF V600E mutation was detected in patients with WVPTCs although three of nine had undergone BRAF V600E mutation analysis in this study: this trend is comparable to the findings of a previous study in which WVPTCs showed fewer mutations than conventional PTCs [11].…”
Section: Discussionsupporting
confidence: 88%
“…Our patients were somewhat older than those reported in previous studies, but showed similar wide range of age distribution [5,6,8,11]. The mean nodule size was smaller than previous studies [5,6], but similar to the recent studies [8,11].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Meanwhile, the heavy lymphoplasmacytic infiltrate is among the defining characteristics of Warthin-like papillary thyroid carcinoma (WL-PTC) in microscopic analysis, and this variant is frequently accompanied by Hashimoto's thyroiditis [12,13]. Given that Hashimoto's thyroiditis with the heavy lymphoplasmacytic infiltration is a common comorbidity of IgG4-RT and WL-PTC, we hypothesize that WL-PTC may have a strong correlation with IgG4-RT.…”
Section: Immunoglobulin G4 (Igg4)-related Dis-ease (Rd) Is a New Clinmentioning
confidence: 96%
“…У хворих з тиреоїдитом Хашимото приб-лизно вдвічі частіше, ніж «класична» зуст-річається мультифокальна ПК [32]; у 3 рази -її Warthin-подібний варіант, за якого му тації BRAF відбуваються рідше, ніж у «кла сичній» [64]. Слід також відмітити, що у пацієнтів з хронічним тиреоїдитом у два рази частіше, ніж у хворих без такого реєстрували фолікулярну будову ПК [14], а її дифузно-склерозуючий варіант, який є однією з найагресивніших форм цього раку, як правило, супроводжується двобічним тиреоїдитом Хашимото [65].…”
unclassified